FATWA MAJELIS ULAMA INDONESIA DALAM PERSPEKTIF PEMBANGUNAN HUKUM RESPONSIF - Ainun Najib (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2012)
In the big state structure of Indonesian, there are two kinds of state structure. The firstone is Infrastructure which is a political life that unseen from the outside yet real and has dynamics, since infra structure is on the society prosperous, so that the action is just seen by observing deeper in the society. While the second one is supra structure (the government sphere) that is a governmental politics life, which can be seen from the outside, because supra structure is more felt and more included in its action. Life pulse of supra structure can be felt in plainÂ  view by anyone. Because this supra structure which directly taking care the society. In this sector, there is state institutes which has role in the process of political life (government).